2004
DOI: 10.1152/ajpheart.00352.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of caveolae in ouabain-induced proliferation of cultured vascular smooth muscle cells of the synthetic phenotype

Abstract: Role of caveolae in ouabain-induced proliferation of cultured vascular smooth muscle cells of the synthetic phenotype. Am J Physiol Heart Circ Physiol 287: H2173-H2182, 2004. First published July 15, 2004 doi:10.1152/ajpheart.00352.2004.-We have shown earlier that low concentrations of ouabain that do not perturb the ionic milieu can initiate proliferation of vascular smooth muscle cells (VSMCs) in the synthetic phenotype from three different species: canine, rodent, and human. This effect occurs by activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
3
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 49 publications
(74 reference statements)
4
45
3
1
Order By: Relevance
“…Xie (60) reported that in addition to promoting ion transport, Na ϩ /K ϩ -ATPase acts as a signal transducer in a cell-specific manner. Allen and co-workers (61,62) demonstrated that the cardiotonic steroid ouabain stimulates vascular smooth muscle cell proliferation, which correlates with increased epidermal growth factor transactivation and Src phosphorylation. Moreover, binding of ouabain to the sodium pump induces the phosphorylation of various MAPKs and subsequently activates the transcription factors AP-1 (activator protein-1) and NFB (63).…”
Section: Discussionmentioning
confidence: 99%
“…Xie (60) reported that in addition to promoting ion transport, Na ϩ /K ϩ -ATPase acts as a signal transducer in a cell-specific manner. Allen and co-workers (61,62) demonstrated that the cardiotonic steroid ouabain stimulates vascular smooth muscle cell proliferation, which correlates with increased epidermal growth factor transactivation and Src phosphorylation. Moreover, binding of ouabain to the sodium pump induces the phosphorylation of various MAPKs and subsequently activates the transcription factors AP-1 (activator protein-1) and NFB (63).…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of cardiac Na/K-ATPase is also related with decreased cardiac contractile function in humans and in animals (1,10,11). Previous reports showed that exposure of cells to low concentrations of cardiotonic steroids (CTS) 2 stimulates cell growth (12)(13)(14). Our recent work also shows that binding of ouabain to Na/K-ATPase in pig renal proximal tubule cells stimulates Src/Akt/mTOR signaling pathways and results in a stimulation of cell growth.…”
mentioning
confidence: 84%
“…Protein A/G plus agarose was purchased from Santa Cruz Biotechnology. 22 Na ϩ was purchased from Perkin-Elmer Life Sciences (Boston, MA). Kidney medullas were prepared by dissection from kidneys.…”
Section: Methodsmentioning
confidence: 99%